1995
DOI: 10.1111/j.1745-4557.1995.tb00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement of Idli Using Extruded Rice Flour

Abstract: The effect of substituting rice with extrusion cooked (75, lOOand 125C) rice flour at 10, 20, 30 and 40% level on the quality of idlis was investigated. Both the levels of substitution and temperature of extrusion had significant effects on the spec@c gravity, acidity and pH of the idli batter, and textural and sensory quality of the idlis. The idlis prepared from idli mix containing rice substituted by 20-30% of rice flour extruded at I25C were most acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The effect of extrusion temperature may be attributed to induced fermentation of the batter as a result of increased quantities of soluble carbohydrates, enzyme susceptible denatured proteins and gelatinized starch. Similar observations have been made earlier (Singh et al 1995). An increase in soluble starch during extrusion of wheat has been reported earlier (Singh and Smith 1997).…”
Section: Ph Of Idli Battersupporting
confidence: 92%
See 2 more Smart Citations
“…The effect of extrusion temperature may be attributed to induced fermentation of the batter as a result of increased quantities of soluble carbohydrates, enzyme susceptible denatured proteins and gelatinized starch. Similar observations have been made earlier (Singh et al 1995). An increase in soluble starch during extrusion of wheat has been reported earlier (Singh and Smith 1997).…”
Section: Ph Of Idli Battersupporting
confidence: 92%
“…The idlis cooking stand was placed in a pressure cooker containing a small quantity of water. The cooker was closed without pressure and the idlis were steamed for 10 min (Singh et al 1995). The expansion (thickness) of idlis was measured at the center with a vernier calliper (Singh et al 1995).…”
Section: Preparation Of Batter and Idlismentioning
confidence: 99%
See 1 more Smart Citation
“…Water soluble high molecular weight polysaccharides have been known for their main application in modification of the rheological properties of aqueous systems, viscosity builders, gelification agents, and stabilizers. [17,18] Arambula et al [7] evaluated the effects of various commercial gums and lime added before and after extrusion in corn and concluded that the addition of hydrocolloids before extrusion gives better results. [7] Hydrocolloids interact with various components of corn (starch, proteins, lipids) producing different effects depending on the type and concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The idli cooking stand was placed in a pressure cooker containing a small quantity of water. The batter was poured into moulds and steamed at 100 °C for 10 min (Singh et al. , 1995).…”
Section: Methodsmentioning
confidence: 99%